A Community Program “Eat Well, See Clearly” For Early Detection Of Diabetic Retinopathy - Sheiladevi; Jiawen Yu; Sathiya Prakash; Hlaing Thaw Dar (Educational Administration: Theory and Practice, 2024)
The “Eat Well, See Clearly” community program, aimed at diabetic populations and those at high risk for diabetic retinopathy (DR) in Selangor, Malaysia, now includes non-diabetic individuals to assess the preventive potential of dietary education. This study utilizes the UK Diabetes and Diet Questionnaire (UKDDQ) to measure dietary habits across these groups within community settings. Purposive sampling targeted adults aged 20 to 50 at eye care centers, ensuring relevance to a demographically diverse group, including those without diabetes. Participants’ dietary knowledge was evaluated using SPSS to analyze questionnaire data, highlighting significant improvements especially among high-risk and diabetic participants. These findings illustrate that enhanced dietary awareness correlates with better management of diabetes and a reduced risk of developing DR. The study supports the integration of structured dietary education into standard care protocols, emphasizing the importance of addressing varied dietary knowledge levels and providing tailored dietary recommendations to manage and potentially prevent DR,integrating structured dietary education into standard care protocols to enhance public health outcomes by effectively managing and potentially reducing DR progression among vulnerable groups.